Sustainable production of high strength fiber reinforced mortars using volcanic ash and magnetized water treatment technology - Mostafa M. Keshta; Mohamed M. Yousry Elshikh; Osama Youssf (Scientific Reports)
Abstract In recent decades, concerns about the high cement consumption and its associated carbon footprint have prompted significant efforts in the construction sector to incorporate alternative materials into cementitious composites. This study focused on the development of a sustainable approach to produce high strength fiber reinforced cementitious mortar (HS-FRCM) and high strength fiber reinforced geopolymer mortar (HS-FRGM). The proposed mortars incorporate volcanic ash (VA) as partial replacements for conventional components, with substitution levels of up to 80%. Furthermore, magnetized water (MW) was utilized as the mixing water in producing both HS-FRCM and HS-FRGM, replacing tap water (TW) for sustainable mortars. Four different curing conditions were used; tap water, seawater, air, and sunlight. The slump values, mechanical performance, durability, and microstructural were conducted and analyzed. The results indicated that VA significantly enhanced HS-FRCM workability by up to 150%, while it had a less pronounced effect on HS-FRGM workability. When 20% VA was used, the 28-day compressive strength of HS-FRCM was not affected, but the compressive strength of HS-FRGM decreased by only 6%. The highest compressive strength was recorded for both HS-FRCM and HS-FRGM when cured in tap water, compared to other conditions of curing. Utilizing MW improved HS-FRCM and HS-FRGM workability by up to 100%, and the compressive strengths increased by as much as 15%. The microstructural analyses revealed that the use of MW resulted in a denser structure with a stronger bond between the fibers and the matrix, as well as fewer microcracks and pores, compared to mixtures prepared with TW. Fourier-transform infrared (FTIR) spectroscopy indicated the effectiveness of using VA and MW in enhancing hydration process.